Infection of Anisakids Larvae in Long Tail Tuna (Thunnus tonggol) In North Persian Gulf - A Eslami; H Sabokroo; SH Ranjbar- Bahadori (Iranian Journal of Parasitology, 2011)
Background: The aim of this paper was to study the prevalence and intensity of Anisakids larvae in the long tail tuna fish captured from Iranian shores of Persian Gulf.Methods: Different organs including skin, abdominal cavity, stomach and intestinal contents, stomach sub serous tissues, liver, spleen, gonads and 20 grams of muscles of 100 long tail tuna fish (Thannus tonggol) caught from waters of the north parts of Persian Gulf were searched for anisakid nematodes larvae. Twenty grams of around the body cavity muscles were digested in artificial gastric juice. Different organs and digested muscles were examined with naked eyes for the presence of anisakids larvae. The collected larvae were preserved in 70% alcohol containing 5% glycerin, and cleared in lactophenol for identification.Results: Our findings revealed that 89% of fish harbored 3rd stage larvae of Anisakis sp. of which 2% were infected with both Anisakis and Raphidascaris. All inspected organs except that of skin were found to be infected, while stomach sub serous tissues were the most infected organ (80%) followed by abdominal cavity (10%), liver (4%), testicle (3%), stomach contents and spleen (2%) and intestinal contents (1%). Intestine and abdominal cavity were the organs harbored Raphidascaris sp. Digested muscles were free of parasite. Mean intensity was low for both species and ranged between 1.5 for Raphidascaris sp. and 3.67 for Anisaki sp.Conclusion: Anisakids larvae especially Anisakis are very prevalent in some fish including tunas of Persian Gulf, and consumption of infected fish if it is not properly cooked may lead to human anisakiasis.